Associative Meaning of Consumers in the Names of Trade Commodities: A Social Semantic Perspective - Gordius Ago; Anna Gustiana Zaenal; La Mahidin; Noviatus Sa’diyah; Muta’allim (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Every commodity traded in the economy has a signifier (symbol or name) that implies a certain meaning. This signifier functions as a communication element between producers and consumers, creating a reciprocal relationship. This study aims to examine the associative meaning of consumer perceptions of product names from a social semantics perspective. The main focus of this research is to identify how the names and signifiers of products can influence consumer perceptions and associations, as well as how social and cultural meanings shape their understanding of a brand or product. This research uses a qualitative approach with data consisting of names and signifiers on commercial commodities. Data sources are taken from products available at Indomaret Wonosari Bondowoso. Data collection is done using the unstructured observation with the researcher observing various commodities at Indomaret Wonosari Bondowoso through note-taking and documentation. Additionally, interviews were conducted with consumers from diverse backgrounds to explore their perceptions further. After data collection, analysis was carried out through classification, verification, tabulation, interpretation, and drawing conclusions based on their categories. The research findings reveal that product names not only serve as markers of identity but also create strong emotional and social associations, such as trust. This, in turn, influences consumer preferences and purchasing decisions. Names that contain cultural elements, symbols, or specific values tend to evoke positive responses and strengthen social attachment with consumers. This study contributes to understanding the importance of brand names in building social relationships between consumers and products, as well as how naming strategies can be utilized in marketing to enhance consumer attraction and loyalty